Performance of Excavated Sulfur-Rich Soil Stabilized with Binder: A Field Study of Mixing Efficiency - Alaleh Ziagharib; Christian Maurice; Josef Macsik; Qi Jia; Jan Laue (Advances in Civil Engineering)
In this study, a mixing procedure of sulfur-rich soil and cement-based binder to enhance the soil’s unconfined compressive strength (UCS) was tested in field conditions for geotechnical applications. The focus was to evaluate uniformity of industrial size soil-binder mixture, blended by existing method. This paper outlined sampling strategy and the number of samples needed for a valid uniformity evaluation. Moreover, this study emphasized the difference between field mixing and laboratory mixture preparation by comparing UCS of stabilized soil samples in the field and UCS of corresponding samples mixed and prepared in the laboratory environment. In the field, soil and cement were blended in two to four stages with 5% and 7% cement—the percentages being based on the soil’s dry weight under field conditions. Samples were taken from the field mixtures after each stage. Since the number of samples needed to be representative of mixture characteristics for large-scale mixing is not standardized, this field experiment included two phases. The first phase was dedicated to finding a sampling strategy for a large soil pile along with measuring UCS of collected samples. In the second phase, sample collection was conducted based on the results of sampling strategy from the first phase. In the laboratory, samples with percentages of binder similar to the amount of binder in the field were also prepared. Both field and laboratory samples were prepared using the tapping method in the laboratory for UCS test. Samples were cured under similar conditions for 28 days. The results showed that the uniformity of mixture improved after each additional mixing stage. In addition, while spots with low UCS were observed in the second mixing step, these spots were eliminated in the third mixing step, and results of the UCS tests were comparatively uniform. Moreover, comparison of the samples revealed that the UCS of the laboratory mixture is higher than that of the field mixture. This showed that even though the UCS is a good standard for comparing the strength of different soils stabilized with different percentages or types of binders in the field mixing, the actual strength of the stabilized mixtures under field circumstances is lower than that in laboratory prepared mixtures.